Call blocking probabilities in a two‐link multirate loss system for Poisson traffic. Issue 4 (1st July 2018) - Sagkriotis, Stefanos G.; Pantelis, Spyros K.; Moscholios, Ioannis D.; Vassilakis, Vassilios G.
Abstract : The authors propose two multirate teletraffic loss models in a two‐link system that accommodates Poisson arriving calls from different service‐classes with different bandwidth‐per‐call requirements. Each link has two thresholds which refer to the number of in‐service calls in the link. The lowest threshold named support threshold, defines up to which point the link can support calls offloaded from the other link. The highest threshold, named offloading threshold, defines the point where the link starts offloading calls to the other link. Two different bandwidth sharing policies are considered: (i) the complete sharing policy, in which a call can be accepted in a link if there exist enough available bandwidth units and (ii) the bandwidth reservation policy, in which an integer number of bandwidth units is reserved to benefit calls of high bandwidth requirements. The two models do not have a product form solution for the steady state probabilities. However, they propose approximate formulas for the calculation of call blocking probabilities. The accuracy of the formulas is verified through simulation and found to be quite satisfactory.